PET/CT in Infection and Inflammation (PET/CT, 2018)
This pocket book provides clinicians with the necessary information to understand the role of FDG PET/CT in infection and inflammation. It will help both in making appropriate imaging requests with adequate clinical information and in interpreting the report. The coverage encompasses a wide range of topics, including the role of PET/CT in pyrexia of unknown origin, vasculitis, autoimmune diseases, prosthetic joint infections, osteomyelitis and diabetic foot, immunodeficiency disease, and vascular graft surgery. The book will be a very useful guide to a great test that can provide significant assistance in patient management. It is published within the Springer series Clinicians' Guides to Radionuclide Hybrid Imaging, in which leading professionals succinctly explain the importance of nuclear medicine in the diagnosis and management of oncological and non-oncological conditions.